Family Planning Village-based Family Education Management - Asvio, Nova; Tamégnon, YAOU; Firman, Arham Junaidi; Ni’mah, Ulfatun (Institut Agama Islam Negeri Lhokseumawe, 2022)
Abstract: The Family Planning Village was launched in 2016 and is used to implement family education to minimize and overcome KKBPK problems. This research explains the management of family education based on Family Planning Village. This research used a qualitative study design which was conducted purposively in 2018. Analysis was done descriptively for qualitative data. The results showed; that the management of family education based on the Family Planning Village includes aspects of conformity criteria for declaration and formation, utilization of family data collection, participation and commitment of local government and across sectors, as well as the form and implementation of family education activities based on the Family Planning Village. Abstrak: Kampung Keluarga Berencana diluncurkan pada tahun 2016 dan digunakan untuk melaksanakan pendidikan keluarga untuk meminimalkan dan mengatasi masalah KKBPK. Penelitian ini menjelaskan tentang manajemen pendidikan keluarga berbasis kampung KB. Penelitian ini menggunakan desain penelitian kualitatif yang dilakukan secara purposive pada tahun 2018. Analisis dilakukan secara deskriptif untuk data kualitatif. Hasilnya menunjukkan; bahwa penyelenggaraan pendidikan keluarga berbasis kampung KB meliputi aspek kriteria kesesuaian deklarasi dan pembentukan, pemanfaatan pendataan keluarga, partisipasi dan komitmen pemerintah daerah dan lintas sektor, serta bentuk dan pelaksanaan kegiatan pendidikan